Secnidazole-Induced Acute Pancreatitis: A New Side-Effect for an Old Drug? - Slim, Raoudha; Ben Salem, Chaker; Zamy, Michele; Fathallah, Neila; Raynaud, Jean-Jacques; Bouraoui, Kamel; Biour, Michel (JOP. Journal of the Pancreas, 2016)
No abstract available. Image: Skeletal formula of secnidazole (Author: Fvasconcellos; Wikimedia Commons)